1991
DOI: 10.1111/j.1469-8137.1991.tb00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of ethene in aerenchyma formation in adventitious roots of rice (Oryza sativa L.)

Abstract: SUMM.\RYTwo varieties of rice (cv, Norin 36 and RB3) were either grown in stagnant or aerated |-strength Hoagland's solution with or without exogenous ethene and a range of silver concentrations (an ethene antagonist), or were grown in flooded and drained soils.With cultivar Norin 36, AgNO^ was very effective in reducing porosity by inhibiting aerenchyma developnnem. This effect was antagonized by gassing with increasing concentrations (1 or 2 jtX 1"') of ethene. The results are consistent, therefore, with rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
0
4

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 23 publications
5
105
0
4
Order By: Relevance
“…In the latter cultivar aerenchyma formation was not affected by ethylene inhibition, which led the authors to conclude that ethylene does not play a role in constitutive aerenchyma development. In response to this paper, Justin and Armstrong (1991b) partly repeated the experiments, but corrected the data for the negative effect of the treatments on the elongation rate of the aerenchymatous roots. With this correction, they concluded that ethylene did play a role.…”
Section: Constitutive Versus Inducible Aerenchymamentioning
confidence: 99%
“…In the latter cultivar aerenchyma formation was not affected by ethylene inhibition, which led the authors to conclude that ethylene does not play a role in constitutive aerenchyma development. In response to this paper, Justin and Armstrong (1991b) partly repeated the experiments, but corrected the data for the negative effect of the treatments on the elongation rate of the aerenchymatous roots. With this correction, they concluded that ethylene did play a role.…”
Section: Constitutive Versus Inducible Aerenchymamentioning
confidence: 99%
“…In Oryza sativa (rice) and Hordeum marinum, suberin and/or lignin in the outer part of roots are thought to contribute to the barrier (Garthwaite et al 2008, Kotula et al 2009a, Kotula et al 2009b, Ranathunge et al 2011 can be detected ). These strategies for acclimating to waterlogged conditions are found in several wetland plants, including rice (Justin and Armstrong 1991, Colmer et al 1998, Colmer et al 2006, Rumex palustris (Visser et al 1995, Visser et al 2000 and H. marinum (Garthwaite et al 2003, Garthwaite et al 2008). However, other crops, such as wheat (McDonald et al 2001b), barley (Garthwaite et al 2003) and maize (Zea mays) (Drew et al 1979, Abiko et al 2012b, can form aerenchyma and newly formed roots, but cannot form an ROL barrier.…”
Section: Introductionmentioning
confidence: 99%
“…In Rumex palustris, ethylene promotes petiole elongation (Voesenek et al, 1993;Cox et al, 2004). In deepwater rice (Oryza sativa), elevated ethylene levels regulate such diverse responses as accelerated growth of mesocotyls, coleoptiles (Ohwaki and Nagao, 1967), internodes (Métraux and Kende, 1983;Kende, 1984a, 1984b;Suge, 1985), and adventitious roots (Bleecker et al, 1986;Lorbiecke and Sauter, 1999) and cell death processes such as those underlying enhanced formation of aerenchyma (Justin and Armstrong, 1991;Inada et al, 2002) and epidermal cell death at the sites where adventitious roots emerge (Mergemann and Sauter, 2000). Since some of these processes need to be tightly coordinated in time and space, the question arises how the ethylene signal is perceived and interpreted by different organs and tissues to allow for these diverse responses in a timely fashion.…”
mentioning
confidence: 99%